2020
DOI: 10.3390/jcm9020489
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 is a Useful Biomarker for Grading Cerebral–Cardiac Syndrome in Patients after Acute Ischemic Stroke

Abstract: This study tested whether the soluble (s)ST2 is a superb biomarker predictive of moderate to severe cerebral–cardiac syndrome (CCS) (defined as coexisting National Institute of Health Stroke Scale (NIHSS) >8 and left-ventricular ejection fraction (LVEF) <60%) in patients after acute ischemic stroke (IS). Between November 2015 and October 2017, a total of 99 IS patients were prospectively enrolled and categorized into three groups based on NIHSS, i.e., group 1 (NIHSS ≤ 8, n = 66), group 2 (NIHSS = 9-15, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…16 Conversely, a report on a smaller cohort from a single-center experience showed that elevated donor's nonhigh sensitivity troponin I serum concentration may be a marker for adverse outcome and increased short-and longterm mortality after HT. 17 Previous reports showed that natriuretic peptides levels were higher in donors whose hearts were declined for transplantation compared with donors whose hearts were considered Recipient M12 28 23 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] .4…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Conversely, a report on a smaller cohort from a single-center experience showed that elevated donor's nonhigh sensitivity troponin I serum concentration may be a marker for adverse outcome and increased short-and longterm mortality after HT. 17 Previous reports showed that natriuretic peptides levels were higher in donors whose hearts were declined for transplantation compared with donors whose hearts were considered Recipient M12 28 23 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] .4…”
Section: Discussionmentioning
confidence: 99%
“…Recently, sST2 has been identified as a useful biomarker for prediction of cerebral-cardiac syn-drome defined as coexisting National Institute of Health Stroke Scale (NIHSS) > 8 and LVEF < 60% in patients after acute ischemic stroke. 27 Thus, sST2 could also be a useful biomarker in the assessment of braindead heart donors and prediction of allograft dysfunction in heart recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic search of online databases yielded 461 non-duplicate records, and 6 articles were acquired by a manual search. After evaluation, 19 articles were included in this systematic review [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] (Fig. 1), of which 10 investigated the value of serum sST-2 measurement in the prediction of the risk of stroke incidence [12][13][14][15][16][17][18][19][20][21], and the remaining 9 evaluated the value of serum sST-2 measurement in the prognosis of post-stroke outcomes [22][23][24][25][26][27][28][29][30].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…sST2 is also studied as a long-term prognostic marker after an episode of ischemic stroke or transient ischemic attack [109]. Also, it can predict moderate to severe cerebral-cardiac syndrome after an ischemic stroke (coexisting NIHSS > 8 and left ventricular ejection fraction < 60%), likely due to its role in inflammatory cardiovascular diseases and myocardial fibrosis [110]. Furthermore, sST2 proved its efficiency in detecting subclinical brain injury after an incident stroke [111].…”
Section: Soluble Form Of the St2 Protein (Sst2)mentioning
confidence: 99%